A model for supplıer selectıon under envıronmental consıderatıons - Yalçın, Ahmet Selçuk (My University, 2017)
Günümüzde, medya, sivil toplum kuruluşları ve bilimsel makaleler sayesinde toplumun ve küresel rekabetçi piyasanın çevresel farkındalığı önemli derecede artmıştır.

Today, the environmental awareness of the society and global competitive market increases considerably thanks to the media, non-governmental organizations and scientific articles.
Keywords: Çevre bilinci; Çevresel yönler; Endüstri, Mühendislik; Farkındalık; İşletmeler; Tedarik zinciri yönetimi; Yeşil tedarik zinciri Green supply chain